Pablo chooses his shoes level 1 - Geatches, Hazel (London : Ladybird books, 2022)
A graded reading series for English Language Teaching (ELT) markets, designed for children learning English as a foreign or second language. Recommended for children aged 3-11, the eight levels of Ladybird Readers follow the CEFR framework (Pre-A1 to A2+) and include language activities that help develop key skills and provide preparation for the Cambridge English tests. This Level 1 Reader is Pre-A1 in the CEFR framework and includes practice for the Cambridge English Pre-A1 Starters tests. Short sentences contain a maximum of two clauses, using the present tense and some simple adjectives. Pablo is going to Granny's house today. "Can we go, too?" ask Pablo's friends. Pablo's blue shoes ask "can we go, too?"
Keywords: English - Book